Autoantibodies against the glial glutamate transporter GLT1/EAAT2 in Type 1 diabetes mellitus—Clues to novel immunological and non-immunological therapies. (March 2022) - Perego, Carla; Di Cairano, Eliana S.; Galli, Alessandra; Moretti, Stefania; Bazzigaluppi, Elena; Centonze, Victoria Frolich; Gastaldelli, Amalia; Assi, Emma; Fiorina, Paolo; Federici, Massimo; Porzio, Ottavia; Bertuzzi, Federico; et al.
Abstract: Islet cell surface autoantibodies were previously found in subjects with type 1 diabetes mellitus (T1DM), but their target antigens and pathogenic mechanisms remain elusive. The glutamate transporter solute carrier family 1, member 2 (GLT1/EAAT2) is expressed on the membrane of pancreatic β-cells and physiologically controls extracellular glutamate concentrations thus preventing glutamate-induced β-cell death. We hypothesized that GLT1 could be an immunological target in T1DM and that autoantibodies against GLT1 could be pathogenic. Immunoprecipitation and ELISA experiments showed that sera from T1DM subjects recognized GLT1 expressed in brain, pancreatic islets, and GLT1-transfected COS7-cell extracts. We validated these findings in two cohorts of T1DM patients by quantitative immunofluorescence assays. Analysis of the combined data sets indicated the presence of autoantibodies against GLT1 in 32 of the 87 (37%) T1DM subjects and in none of healthy controls (n = 64) (p < 0.0001). Exposure of pancreatic βTC3 cells and human islets to purified IgGs from anti-GLT1 positive sera supplemented with complement resulted in plasma membrane ruffling, cell lysis and death. The cytotoxic effect was prevented when sera were depleted from IgGs. Furthermore, in the absence of complement, 6 out of 16 (37%) anti-GLT1 positive sera markedly reduced GLT1 transport activity in βTC3 cells by inducing GLT1 internalization, also resulting in β-cell death. In conclusion, we provide evidence that GLT1 is a novel T1DM autoantigen and that anti-GLT1 autoantibodies cause β-cell death through complement-dependent and independent mechanisms. GLT1 seems an attractive novel therapeutic target for the prevention of β-cell death in individuals with diabetes and prediabetes. Graphical Abstract: ga1 Highlights: The excitatory amino acid transporter GLT1/EAAT2 is a glutamate transporter expressed at the plasma membrane of pancreatic β-cells. GLT1/EAAT2 controls the extracellular glutamate concentration in the islet of Langerhans microenvironment. Autoantibodies directed against GLT1/EAAT2 are present in almost 40% of Type 1 Diabetic patients. Anti-GLT1/EAAT2 autoantibodies cause β-cell death through complement-dependent and independent mechanisms. GLT1/EAAT2 is an attractive pharmacological target for the prevention and treatment of Type 1 diabetes mellitus.